Változások a pulmonalis hypertonia 2015. évi irányelvében - Forster Tamás (Akadémiai Kiadó, 2016)
The new 2015 ESC/ERS Guideline refined the diagnostic criteria of pulmonary hypertension. A new diagnostic algorithm is suggested. The therapeutic algorithm is renewed on the basis of newly registered drugs. Besides the usual sequential combination, the immediate (initial) combination is proposed as an alternative way. Pulmonary hypertension should be treated in expert referral centers.